Spectral analysis of antenna RF-current in the torsatron U-2M - Berezhnyj, V.L.; Filippov, V.V.; Berezhnaya, I.V. (Вопросы атомной науки и техники, 2014)
The paper deals with the spectral analysis of the antenna RF-current in the torsatron U-2M to elucidate the possibility of improving the efficiency of the RF-technique for plasma formation and heating. The present results show that the improvement in the efficiency of RF power input into the plasma calls for upgrading of both the generator system and the design of the RF antenna and its protection in order to reduce nonlinear interaction of RF waves with the near-antenna plasma.